2017
DOI: 10.1155/2017/1987456
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Geometrical and Material Nonlinear Energy Sink with Piezoelectric Material Energy Harvester

Abstract: This paper presents a novel design by integrating geometrical and material nonlinear energy sink (NES) with a piezoelectric-based vibration energy harvester under shock excitation, which can realize vibration control and energy harvesting. The nonlinear spring and hysteresis behavior of the NES could reflect geometrical and material nonlinearity, respectively. Two configurations of the piezoelectric device, including the piezoelectric element embedded between the NES mass and the single-degree-of-freedom syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The multiscale method was used to solve the equations of nonlinear energy harvesting systems [109,110]. Geometric nonlinearity and material NESs were integrated with the piezoelectric vibration energy harvester to realize vibration control and energy harvesting of singledegree-of-freedom structures [111]. By using the Runge- and (c) schematic diagram [80].…”
Section: Nes Performance Balance In Vibration Suppression and Energymentioning
confidence: 99%
“…The multiscale method was used to solve the equations of nonlinear energy harvesting systems [109,110]. Geometric nonlinearity and material NESs were integrated with the piezoelectric vibration energy harvester to realize vibration control and energy harvesting of singledegree-of-freedom structures [111]. By using the Runge- and (c) schematic diagram [80].…”
Section: Nes Performance Balance In Vibration Suppression and Energymentioning
confidence: 99%
“…In recent years, piezoelectric materials and giant magnetostrictive-piezoelectric material have been applied in energy harvesting research due to the superior energy harvesting efficiency and are simultaneously combined with the NES for vibration energy harvesting. [93][94][95][96][97] Ahmadabadi and Khadem 98 and Zhang et al 99 constructed a vibration suppression and energy harvesting system composed of grounded and ungrounded NES with piezoelectric materials. The former showed that the energy harvesting efficiency of grounded device was better.…”
Section: Energy Harvestingmentioning
confidence: 99%
“…Some of them are called Energy Dissipation Measure (EDM), energy dissipation ratio, and the instantaneous total energy stored in the NES. [43][44][45][46][47] Grounded NESs have been the subject of different studies in the past two decades and several investigations regarding different configurations of the main system and/ or the grounded NES, comparison of the grounded and ungrounded NESs for vibration mitigation, energy harvesting, and optimization of the vibration absorbers have been performed in recent years and in view of authors, there are still rooms for more research. For example, 48 is one of the most recent papers in this context where, for pipe conveying fluids, the performance of grounded NES was compared with ungrounded one.…”
Section: Introductionmentioning
confidence: 99%